The impact of after-hours messaging on job stress and burnout among Taiwan’s border police: the roles of social support and coping strategies - Nein-Tsu Chiang; Rui-Hsin Kao; Hsiang-Yu Ma; Cheng-Chung Cho (Humanities & Social Sciences Communications)
Abstract With the advancement of technology, communication software is increasingly facilitating interaction between organizations and employees. However, its unrestricted accessibility often blurs the line between work and personal life. This study investigates how after-hours work requests from supervisors through messaging software (SMAHWRUCS) affect the job stress of frontline border police in Taiwan. It explores the roles of social support, team interactions, and individual coping strategies in reducing job stress, burnout, and overall well-being. The results of a survey of 467 police officers highlighted that after-hours work demands increase job stress, leading to increased burnout and decreased well-being. Individual coping strategies, whether approach-oriented or avoidance-oriented, exacerbate or alleviate these effects, respectively. Moreover, social support and team interactions become key factors in reducing job stress and its negative consequences. This study highlights the importance of creating a supportive environment, promoting effective team dynamics, and guiding employees to adopt appropriate stress coping strategies within the organization.